2020
DOI: 10.1002/jpen.1870
|View full text |Cite
|
Sign up to set email alerts
|

Enteral Nutrition Administration Record Prescribing Process Using Computerized Order Entry: A New Paradigm and Opportunities to Improve Outcomes in Critically Ill Patients

Abstract: Background Prevalence of malnutrition has been reported in 60% of hospitalized and up to 78% of patients admitted to intensive care units. Malnutrition has been associated with complications, such as infection, increased hospital length of stay, morbidity, and mortality. Nutritional support has been shown to reduce avoidable readmissions, pressure ulcers, malpractice claims, and hospital costs. Creating a new electronic nutrition administration record (ENAR) with a linked nutrition tab within the electronic he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 18 publications
0
24
0
Order By: Relevance
“…The Meehan study reported that the use of MAR for ONS streamlined the process for administration and documentation of ONS and allowed for better monitoring, reduced length of hospital stay, reduced prevalence of pressure ulcer, reduced 30‐day readmissions, and reduced costs of care 8 . Another report found that after inclusion of ONS on the MAR, more patients reported being offered the ONS product ( P = .01), and more patients (5% before and 86% after) reported being offered the correct type, amount, and frequency of nutritional products ( P = .01) 25,26 . van den Berg and colleagues (2015) reported on a randomized controlled trial assessing ONS consumption if patients were given ONS during medication administration.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The Meehan study reported that the use of MAR for ONS streamlined the process for administration and documentation of ONS and allowed for better monitoring, reduced length of hospital stay, reduced prevalence of pressure ulcer, reduced 30‐day readmissions, and reduced costs of care 8 . Another report found that after inclusion of ONS on the MAR, more patients reported being offered the ONS product ( P = .01), and more patients (5% before and 86% after) reported being offered the correct type, amount, and frequency of nutritional products ( P = .01) 25,26 . van den Berg and colleagues (2015) reported on a randomized controlled trial assessing ONS consumption if patients were given ONS during medication administration.…”
Section: Discussionmentioning
confidence: 99%
“…There are limited studies on the use of MAR for administration and documentation ONS. Of the few published studies, benefits such as improved administration and documentation, reduced waste, and improved patient outcomes have been reported; however, all had methodological limitations (small sample size, 1 cohort) 8,25–27 . Meehan et al (2016) reports on a nurse‐led quality improvement study related to use of MAR systems to administer and document ONS for hospital patients 8 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, capturing the EN product used as well as documenting the amount used is important for the overall care of patients. To address these issues, Kamel et al demonstrated the steps for development of an electronic nutrition administration record (ENAR) with a linked nutrition tab in their EHR [61]. Working with the EHR vendor, they were able to create order panels that standardized the EN ordering process.…”
Section: Digital Technology and Nutrition Supportmentioning
confidence: 99%